Introduction to Concurrency Theory : Transition Systems and CCS - Gorrieri, Roberto; Versari, Cristian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents the fundamentals of concurrency theory with clarity and rigor. The authors start with the semantic structure, namely labelled transition systems, which provides us with the means and the tools to express processes, to compose them, and to prove properties they enjoy. The rest of the book relies on Milner's Calculus of Communicating Systems, tailored versions of which are used to study various notions of equality between systems, and to investigate in detail the expressive power of the models considered. The authors proceed from very basic results to increasingly complex issues, with many examples and exercises that help to reveal the many subtleties of the topic. The book is suitable for advanced undergraduate and graduate students in computer science and engineering, and scientists engaged with theories of concurrency.
Introduction -- Transition Systems and Behavioral Equivalences -- CCS: A Calculus of Communicating Systems -- Algebraic Laws, Congruences and Axiomatizations -- Additional Operators -- Multi-CCS -- Glossary -- References -- Index.
Keywords: Information theory; Computer science; Software engineering; Logic, Symbolic and mathematical; Theory of Computation; Mathematics of Computing; Software Engineering/Programming and Operating Systems; Mathematical Logic and Foundations